Sex and gender differences in social participation among community-dwelling older adults: a systematic review - Ong, Chuan Hong; Pham, Bang Linh; Levasseur, Mélanie; Tan, Guang Rong; Seah, Betsy (Frontiers in Public Health, 2024)
Background: Frequent social participation among older adults is associated with greater health.Although understanding how sex and gender influence social participation is important, particularly in developing sex-inclusive health promotion and preventive interventions, little is known about factors influencing engagement of older women and men in social activities.Aim: This study thus aimed to examine factors influencing social activities of older women and men.Methods: A mixed-method systematic review was conducted in nine electronic databases from inception to March 2023. The studies had to define social participation as activities with others and examine its influencing factors among community-dwelling older women and men. Data were analysed using convergent synthesis design from a socio-ecological perspective.Results: Forty-nine studies, comprising 42 quantitative, five qualitative and two mixed method design were included. Themes identified concerned: (a) sociodemographic factors, (b) personal assets, (c) interpersonal relationships and commitments, (d) physical environment, and (e) societal norms and gender expectations. The findings identified the heterogeneous needs, preferences and inequalities faced by older women and men, considerations on sociocultural expectations and norms of each gender when engaging in social activities, and the importance of having adequate and accessible social spaces. Overall, this review identified more evidence on factors influencing social participation among women than in men.Special attention is needed among community care providers and healthcare professionals to co-design, implement or prescribe a combination of sex and gender-specific and neutral activities that interest both older women and men. Intersectoral collaborative actions, including public health advocates, gerontologists, policymakers, and land use planners, are needed to unify efforts to foster social inclusion by creating an age-friendly and sustainable healthy environment. More longitudinal studies are required to better understand social participation trajectories from a sex and gender perspective and identify factors influencing it.